Voluntary Employer-Provided Severance Pay - Donald O. Parsons (Institute of Labor Economics (IZA), 2017)
Employer-provided severance pay in the U.S. emerged among salaried workers during the Great Depression as an alternative to modest advance notice and expanded in the late 1950s and 1960s, especially among union (hourly) workers. A variety of sources are employed to estimate variations in severance coverage and design over the remainder of the 20th Century. The Bureau of Labor Statistics provided coverage estimates from 1980 to 2000, but these offered little information on severance plan structures, forcing reliance on surveys by private, for-profit management consulting firms. Although the studies differ in sample and survey instrument design, they broadly reveal a standard benefit form –essentially scheduled wage insurance, similar to severance plans mandated internationally. Coverage is another matter, with voluntary coverage narrowly focused on firms/workers vulnerable to large job displacement wage losses, while mandated coverage is quite broad. Labor market events of the new century highlight the limits of standard benefit schedules as wage insurance, whether voluntary or mandated.
Keywords: J65; J32; J33; 330; severance pay; wage insurance; unemployment insurance; layoff; job displacement